Hydrolysis Temperature dependent Structural, Optical Band Gap and the associated Urbach Tail Energy of Cellulose Nanocrystals Fabricated from Water Hyacinth - Adem, Jack A.; Agumba, John; Barasa, Godfrey .O.; Ochung, Angeline A. (European Journal of Applied Sciences, 2022)
This study has thus systematically investigated the fingerprints of hydrolysis temperature on the optical and structural properties of the resultant CNCs. From the study, it was observed that increase in hydrolysis temperature decreases the grain size from 21.7 nm to 19.3 nm. However, crystallinity increased from 57.9% to 60.3% as calculated using Scherrer equation. By performing UV-Vis spectroscopy, the value of the peak wavelength for maximum absorption, Xc increased from 247.52 nm for 50oC to 247.76 for 90oC. The value of FWHM equally increased from 12.17 nm for 50oC to 13.48 nm for 90oC. Additionally, increasing hydrolysis temperature from 50oC to 90oC decreased the bandgap energy, Eg from 5.31 eV to 5.14 eV. However, the Urbach energy increased from 116 meV to 217 meV respectively. From a plot of Eg verses Eu, the optical band gap energy of the CNCs when there is no disorder in their microstructure was found to be 5.43 eV. The CNCs have zero optical band gap energy when hydrolysis is done at 1297.6oC. Further, we have shown that the Urbach energy is absent when hydrolysis is done at 14.23oC. This is the energy when the localized defect states in an optical band gap region are completely screened. The hydrolysis temperature dependent increase in the electronic disorder in the crystal (Urbarch energy) with increase in associated band gap energy has thus been estimated to account for the optical disorder in the CNCs.